2021
DOI: 10.1021/acs.jpcc.1c00073
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Structural and Mechanical Properties of Coiled Carbon Nanotubes with NSGA-II and Reactive Molecular Dynamics Simulation

Abstract: Coiled carbon nanotubes (CCNTs) have increasingly become a vital factor in the new generation of nanodevices and energy-absorbing materials due to their outstanding properties. Here, the multiobjective optimization of CCNTs is applied to assess their mechanical properties. The best trade-off between conflicting mechanical properties (e.g., yield stress and yield strain) is demonstrated and the optimization of the geometry enables us to find the astonishing CCNTs with a stretchability of 400%. These structures … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…All the atomic structures of coiled CNTs with various parameters via PFC modeling can be found at https://github.com/YanChen32/Coiled‐carbon‐nanotubes.git. Compared with previous works, [ 32,46 ] the atomic structures of coiled CNTs obtained by PFC modeling possess more perfect and smooth helical configurations, covering an arbitrary combination of geometrical parameters, i.e., CNT radius r , coil pitch l , and coil radius R , as shown in Figure 1c.…”
Section: Models and Methodsmentioning
confidence: 87%
“…All the atomic structures of coiled CNTs with various parameters via PFC modeling can be found at https://github.com/YanChen32/Coiled‐carbon‐nanotubes.git. Compared with previous works, [ 32,46 ] the atomic structures of coiled CNTs obtained by PFC modeling possess more perfect and smooth helical configurations, covering an arbitrary combination of geometrical parameters, i.e., CNT radius r , coil pitch l , and coil radius R , as shown in Figure 1c.…”
Section: Models and Methodsmentioning
confidence: 87%
“…19,20 Chuang's model has been widely used in previous investigations to study mechanical properties. 21,[37][38][39]48,59 Based on this model, CCNTs contain non-hexagonal defects in the inner and outer parts of the coils, and the four fundamental parameters (s, n77, n75, and n55) determine the placement of these defects in the structures. In this way, placing heptagonal defects in the internal side and pentagonal defects in the external side of coils create concavity (negative curvatures) and convexity (positive curvatures) in the internal and external parts of CCNTs.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, they reported that the yield stress and strain decrease with increasing temperature. In another research study, 39 they proposed several theoretical equations based on fitting a continuum model to MD simulation results. They illustrated that large CCNTs have relatively high amounts of yield point values compared to small CCNTs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation